Perancangan tata letak workshop menggunakan metode Systematic Layout Planning (SLP) di pergudangan Central Industrial Park - Nuraini, Siti Arifah; Dewi, Sinta (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
In the industrial world, the issue of factory layout and the layout of production facilities and equipment is one that plays an important role in increasing company productivity. Inappropriate layout can cause material transfer time to be ineffective due to the long distance between stations. Central Industrial Park (CIP) is a warehouse area in Sidoarjo Regency. This research aims to improve and create a new layout of facilities in the workshop warehouse in the CIP area. Data processing was carried out using the Systematic Layout Planning (SLP) method with the help of Blocplan 90 software. This research produced Adj values. Score of 0.80. The R-score value is 0.78 and has an R-Dist score value of 355. The results of research on layout improvements found a length of 18.5 meters and a width of 15 meters.